MODIFICATION AND CHARACTERIZATION OF TASIKMALAYA NATURAL ZEOLITES WITH Fe2O3 - Oktaviani, Reka; Hindryawati, Noor; Panggabean, Aman Sentosa (JURNAL ATOMIK, 2019)
Research on natural zeolite has been carried out as a porous material modified by Fe2O3 semiconductor material. Starting with natural zeolite preparation, dealumination by activating it using HCl solution, modifying natural zeolite with Fe2O3 using FeCl3 and NaOH solution, then characterized using X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and test the surface area using a Methylene Blue solution. The results of the XRF analysis showed that the composition of Fe2O3 increased after it was modified to 38.022%, which was previously namely 3.193%. The results of SEM analysis showed changes in the morphology of natural zeolites after being modified with Fe2O3. The results of the XRD analysis showed that there was a diffraction peak which provided information that the sample contained Fe2O3. Zeolite-Fe2O3 has a surface area of ??110,2707 m2/g. Keywords : natural zeolite, Fe2O3, semiconduktor